The Early Growth and Development of 10 Genotypes Gajah Ginger as Intercrops System in Jatropha curcas Plantation - Prasetyo, Yudi; Zainudin, Agus; Muhidin, Muhidin (Universitas Muhammadiyah Malang, 2020)
Ginger (Zingiber officinale Rosc.) is one of the medicinal plants and can be processed into products such as essential oils and starches. Ginger was planted under a tree because it has a good sunlight tolerant plant. Ginger can grow and develop normally, even in low light intensity. Indonesia has a lot of land with shade conditions and potential for ginger production. It can be supported to increase national ginger production. This study aims to assess the growth and development of ginger in Gajah variety, with several genotypes, that are cultivated as intercropping at Jatropha curcas. The study was conducted in Jatropha plantation at 2.144 dap age, which is located at Desa Kedungpenggaron, Kec. Kejayaan, Pasuruan city (117 m above sea level, with coordinates 7 ° 46'18.6